The three faces of riboviral spontaneous mutation: spectrum, mode of genome replication, and mutation rate. - Libertad García-Villada; John W Drake (PLoS Genetics)
Riboviruses (RNA viruses without DNA replication intermediates) are the most abundant pathogens infecting animals and plants. Only a few riboviral infections can be controlled with antiviral drugs, mainly because of the rapid appearance of resistance mutations. Little reliable information is available concerning i) kinds and relative frequencies of mutations (the mutational spectrum), ii) mode of genome replication and mutation accumulation, and iii) rates of spontaneous mutation. To illuminate these issues, we developed a model in vivo system based on phage Qß infecting its natural host, Escherichia coli. The Qß RT gene encoding the Read-Through protein was used as a mutation reporter. To reduce uncertainties in mutation frequencies due to selection, the experimental Qß populations were established after a single cycle of infection and selection against RT(-) mutants during phage growth was ameliorated by plasmid-based RT complementation in trans. The dynamics of Qß genome replication were confirmed to reflect the linear process of iterative copying (the stamping-machine mode). A total of 32 RT mutants were detected among 7,517 Qß isolates. Sequencing analysis of 45 RT mutations revealed a spectrum dominated by 39 transitions, plus 4 transversions and 2 indels. A clear template•primer mismatch bias was observed: A•C>C•A>U•G>G•U> transversion mismatches. The average mutation rate per base replication was ≈9.1×10(-6) for base substitutions and ≈2.3×10(-7) for indels. The estimated mutation rate per genome replication, μ(g), was ≈0.04 (or, per phage generation, ≈0.08), although secondary RT mutations arose during the growth of some RT mutants at a rate about 7-fold higher, signaling the possible impact of transitory bouts of hypermutation. These results are contrasted with those previously reported for other riboviruses to depict the current state of the art in riboviral mutagenesis.